2002
DOI: 10.1128/mcb.22.4.1218-1232.2002
|View full text |Cite
|
Sign up to set email alerts
|

The AT-Hook Protein D1 Is Essential for Drosophila melanogaster Development and Is Implicated in Position-Effect Variegation

Abstract: We have analyzed the expression pattern of the D1 gene and the localization of its product, the AT hookbearing nonhistone chromosomal protein D1, during Drosophila melanogaster development. D1 mRNAs and protein are maternally contributed, and the protein localizes to discrete foci on the chromosomes of early embryos. These foci correspond to 1.672-and 1.688-g/cm 3 AT-rich satellite repeats found in the centromeric heterochromatin of the X and Y chromosomes and on chromosomes 3 and 4. D1 mRNA levels subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 58 publications
4
75
1
Order By: Relevance
“…It also binds to the complex 1.688 g/cm 3 satellite, which is chiefly a 359-bp repeat and 69% AT in composition. In agreement with this work, a heterochromatic localization was observed for D1 in both mitotic and interphase diploid cells by immunostaining (Renner et al 2000; 1 Aulner et al 2002). As revealed by immunostaining to salivary gland polytene chromosomes, D1 shows a less predominant localization to euchromatic sites, which could reflect its binding to interspersed AT tracts (Alfageme et al 1976;Rodriguez Alfageme et al 1980).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…It also binds to the complex 1.688 g/cm 3 satellite, which is chiefly a 359-bp repeat and 69% AT in composition. In agreement with this work, a heterochromatic localization was observed for D1 in both mitotic and interphase diploid cells by immunostaining (Renner et al 2000; 1 Aulner et al 2002). As revealed by immunostaining to salivary gland polytene chromosomes, D1 shows a less predominant localization to euchromatic sites, which could reflect its binding to interspersed AT tracts (Alfageme et al 1976;Rodriguez Alfageme et al 1980).…”
supporting
confidence: 70%
“…To this end, I examined the lethality of the P-insertion lines, carried out genetic screens to isolate D1 null mutants, and performed genetic tests to study the effects of loss of D1 protein. Although other investigators reported that the D1 gene is essential (Aulner et al 2002), the studies described herein demonstrated that D1 is not required for viability or fertility. In addition, it is not a suppressor of position effect variegation.…”
mentioning
confidence: 60%
“…Although homeobox proteins have been established as master gene transcription factors [46], DNA architecturemodulating AT-hook proteins constitute an evolutionarily conserved family with analogous global gene-regulation functions [1,2,4,6,9]. In accordance with this notion, AT-hook proteins bind a broad spectrum of AT-rich sequence-containing promoters [5] and regulate pathwayspecific gene expression networks [3,8,47,48].…”
Section: Discussionmentioning
confidence: 80%
“…Examples of such regulators include AThook proteins, a family of transcription factors that target genes with A/T-rich promoters [4][5][6] and orchestrate their activation or repression [7][8][9][10][11]. Notably, AT-hook proteins have been mainly recognized within the high mobility group (HMG) family [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Another 1982 study by Levinger and myself showed that the D1 protein preferentially binds to (A ϩ T)-rich DNA in vitro, including the 1.672 and 1.688 satellite DNA repeats, and is a component of isolated nucleosomes containing these centromeric satellite DNAs (106). Later studies (107,108) indicated that D1, which contains 10 copies of the "AT-hook" domain, a motif that interacts with the minor groove of AT-rich DNA, is a part of heterochromatin-associated complexes that mediate transcriptional repression.…”
Section: Mdr1 a Multidrugmentioning
confidence: 99%